Narratives of Pain: Trauma and the Healing Power of Writing - Lisa Tyler (Journal of the Assembly for Expanded Perspectives on Learning, 1999)
Writing about traumatic events is useful, healing, and meaningful, and such work deserves a place in the composition classroom.